2011
DOI: 10.1016/j.topol.2011.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Rothberger bounded groups and Ramsey theory

Abstract: OverviewBoundedness properties in topological groups are counterparts for covering properties in general topological spaces:Guran's notion of ℵ 0 -boundedness is a counterpart of the Lindelöf covering property [9], while Okunev's notion of o-boundedness (named Menger-boundedness by Kočinac, who introduced this notion independently) and Tkachenko's corresponding property of strict o-boundedness are counterparts of σ -compactness [10]. In this paper we consider a boundedness property which approximates Borel's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…✷ There are many ZFC examples of Lindelöf P-spaces. For example in [30] it is shown that for each uncountable cardinal number κ there is a T 3 1 2 Lindelöf P -group of cardinality κ on which TWO has a winning strategy in the game G ω 1 (Ω, Γ). Since the topology is the G δ topology, this means that in these examples TWO has a winning strategy in the game G 1 (G K , G Γ ).…”
Section: Productively Lindelöf Spacesmentioning
confidence: 99%
“…✷ There are many ZFC examples of Lindelöf P-spaces. For example in [30] it is shown that for each uncountable cardinal number κ there is a T 3 1 2 Lindelöf P -group of cardinality κ on which TWO has a winning strategy in the game G ω 1 (Ω, Γ). Since the topology is the G δ topology, this means that in these examples TWO has a winning strategy in the game G 1 (G K , G Γ ).…”
Section: Productively Lindelöf Spacesmentioning
confidence: 99%
“…In some classes of topological groups R-boundedness has been characterized Ramsey-theoretically. For example, in [19] it was done for the class of σ-compact metrizable groups.…”
Section: Discussionmentioning
confidence: 99%
“…This result was proven in [36], Theorem 9, for the special context of σ-compact metric spaces. Its generalization to Theorem 3.6 was briefly explained previously in Theorem 3 of [40]. For the reader's convenience we provide a proof of Theorem 3.6 here.…”
Section: A Theorem Of Fp Ramseymentioning
confidence: 92%
“…For example Example 2.7. In [40] Proposition 6 it is shown that there is for each uncountable cardinal κ a T 0 topological group that has cardinality κ, does not embed as a closed subgroup into any σ-compact group, and yet TWO has a winning strategy in the game G 1 (O nbd , O) in this group. Even more, TWO has a winning strategy in the game G 1 (O, O) in this group.…”
Section: An Infinite Game and Covering Propertiesmentioning
confidence: 99%